Organ transplantation and gender differences: a paradigmatic example of intertwining between biological and sociocultural determinants. Issue 1 (December 2016) - Puoti, Francesca; Ricci, Andrea; Nanni-Costa, Alessandro; Ricciardi, Walter; Malorni, Walter; Ortona, Elena
Abstract Organ transplantation, e.g., of the heart, liver, or kidney, is nowadays a routine strategy to counteract several lethal human pathologies. From literature data and from data obtained in Italy, a striking scenario appears well evident: women are more often donors than recipients. On the other hand, recipients of organs are mainly males, probably reflecting a gender bias in the incidence of transplant-related pathologies. The impact of sex mismatch on transplant outcome remains debated, even though donor-recipient sex mismatch, due to biological matters, appears undesirable in female recipients. In our opinion, the analysis of how sex and gender can interact and affect grafting success could represent a mandatory task for the management of organ transplantation.